The PRESET-Score: the extrapulmonary predictive survival model for extracorporeal membrane oxygenation in severe acute respiratory distress syndrome - Montero, Santiago; Slutsky, Arthur S.; Schmidt, Matthieu (Journal of Thoracic Disease; Vol 10, Supplement 17 (June 20, 2018): Journal of Thoracic Disease, 2018)
Acute respiratory distress syndrome (ARDS) is one of the leading causes of mortality in the intensive care unit (ICU) (1,2), with a mortality reaching 46% in its most severe forms (1). In an attempt to decrease this high mortality, over the past decade, clinicians have increasingly been using extracorporeal membrane oxygenation (ECMO).